Green software defined radios : enabling seamless connectivity while saving on hardware and energy - Perre, Liesbet van der (Springer, 2017)
The increasing need for functional flexibility (the number of wireless standards is large and expected to grow) and the exploding cost of system-on-chip design will make implementation of wireless standards on reconfigurable radios the only viable option in the future. Software Defined Radios (SDRs) will offer higher flexibility at lower cost. Moreover, they are key enablers in the realization of cognitive radios, which will enable more efficient use of network and spectral resources. Green SDRs will be essential, to save on crucial and scarce resources: energy and spectrum. Green Software Defined Radios gives insight in the trends asking for green SDRs. The essential ingredients of these radios are elaborated on. Specifically, design solutions and approaches for energy-scalable SDRs, both for the radio front-end and the digital baseband (including hardware and software), are explained. Intelligent (cross-layer) control is introduced as the key to achieve energy efficient operation and seamless connectivity. Last but not least the book focuses on cognitive radios, opening a new wireless order. These radios build on SDR platforms, enhanced with a sensing engine and intelligent control.